(untitled) (Altre Modernità, 2018)
Esterino Adami, Francesca Bellino & Alessandro Mengozzi (eds.), Other Worlds and the Narrative Construction of Otherness (Milano, Mimesis, 2017, 210 pp. ISBN 978-886-977-095-1) by Nicoletta Vallorani